Nanotechnology-based disinfectants and sensors for SARS-CoV-2 - Talebian, Sepehr (2020)
Funding: J.C. acknowledges the European Research Council Starting Grant (ERC-StG-2019-848325). F.S. acknowledges the Swiss National Science Foundation Sinergia Program. A.S. acknowledges the support of ERC-STG-2015-680242 and of the Israel Ministry of Science and Technology COVID19 Grant. S.T. and G.G.W. are grateful for funding from the Australian Research Council Centre of Excellence program (project no. CE 140100012).